The emerging roles and mechanism of N6-methyladenosine (m6A) modifications in urologic tumours progression - Zhu, Wenhao; Zhao, Renshan; Guan, Xiaomin; Wang, Xu (Frontiers in Pharmacology, 2023)
Prostate cancer (PCa), bladder cancer (BC), and renal cell cancer (RCC) are the most common urologic tumours in males. N6-methyladenosine (m6A), an adenosine N6 methylation, is mammals' most prevalent RNA modification. There is increasing evidence m6A plays a crucial role in cancer development. In this review, we comprehensively analyzed the influence of m6A methylation on PCa, BC, and RCC and the relationship between the expression of relevant regulatory factors and their development and occurrence, which provide new insights and approaches for the early clinical diagnosis and targeted therapy of urologic malignancies.